The Analysis of Working Time Allocation and Income of Rice Farmers in Pulogede Village Tuban District - Dinda Rhaima Ladisa Putri; Endang Yektiningsih; Mubarokah Mubarokah (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
Unoptimal use of farmers' time leads to low income earned by farmers. The study aims to analyze the working hours of rice farmers, analyze factors that influence the allocation of rice farmers, time, and analyze farmers' income in rice farms. The study was conducted in January-March 2024 in Pulogede, Tambakboyo district, Tuban district. The sampling method is a random proportional sample with 71 farmers as respondents—primary data collection through interviews assisted by questionnaires. The first objective was quantified descriptively, the second used double linear regression analysis using SPSS analysis tools with variables independent of age, land area, working experience, working income, family dependence, and education, and the third objective calculated rice farmer income. The study found that the farmer's working time allocation was influenced by age, size of land, farming experience, farmers' income, number of dependent families, and education. The income earned by the rice farmer is IDR8.870,880/ season.